Peningkatan Pengetahuan Lansia dengan Hipertensi Menggunakan Booklet QR-Code Terintegrasi Website - Muhammad Dodik Prastiyo; Azizah Khoirotun Ni'mah; Fino Ardiansyah; M Nur Cahyo Firdaus; Rani Rakhmawati (Poltekkes Kemenkes Gorontalo, 2023)
Background: Hypertension is still a major burden of health financing around the world known as the silent killer becauseit causes sufferers to be unaware of the threat of complications such as stroke, myocardial infarction, kidney failure, andheart failure that can result in death. The World Health Organization (WHO) reported that in 2019, the number of people with hypertension in the world was 1.13 billion. The high prevalence of hypertension can be lowered by self-managementbehavior.Objective: Knowing the effect of hypertension self-management behavior education based on Booklet QR code integratedWeb health on the elderly in Bakalan Krajan Hamlet, Malang City.Method: The sample in this study was 10 hypertensive patients from Bakalan Krajan Hamlet, Malang City. The sampling technique uses purposive sampling and Quasy experimental one-group pretest-posttest research design.Results: This study used the Wilcoxon signed–rank test because the data was not normally distributed to determine thedifference between pretest and post-test dependent samples. The results showed significant p = 0.046 with an alpha valueof p < 0.05.Conclusion: There is an influence of hypertension education based on self-management behavior based on Web healthintegrated QR code Booklet on the elderly in Bakalan Krajan Hamlet, Malang City. Future studies are needed to involvemore samples.